Pengaruh Konsenetrasi Lesitin dan Carboxymethyl Cellulose (CMC) terhadap Karakteristik Fisik Edible Film Berbasis Pati Sagu - A. Hermina Julyaningsih; Andi Nur Faidah Rahman; Febriana Intan Permata Hati (Jurnal Penelitian Pendidikan IPA, 2025)
Microplastics have begun to be detected in human food sources such as water and marine fish. One of the solutions that has been increasingly studied and developed is edible film. Sago starch holds significant potential to be developed as a raw material for edible film production. However, the physical characteristics of edible films made from pure sago starch tend to be brittle, water-soluble, and mechanically weak. To enhance their physical quality, additives such as lecithin and carboxymethyl cellulose or CMC are required. This study aimed to evaluate the physical properties of sago-based edible films, including thickness, solubility, tensile strength, and water vapor transmission rate (WVTR), at various concentrations of lecithin (0.3%, 0.5%, 0.7%, and 1.5%) and CMC (0.1%, 0.3%, 0.5%, and 0.7%) to determine the optimal formulation for use as food packaging. The research employed experimental research, using Completely Randomized Design. Data were analyzed using one-way ANOVA followed by Duncan’s post hoc test. Results showed that both lecithin and CMC concentrations significantly affected the physical characteristics of the edible films. Based on these observations, treatment B4 was identified as having the best overall physical characteristics, providing a good balance between mechanical strength and water resistance with adequate film thickness.